The original Mediterranean cuisine : medieval recipes for today - Santich, Barbara (Sheffield, UK ; Bristol, CT : Equinox Publishing Ltd, 2018)
"The Original Mediterranean Cuisine is both culinary history and cookbook, with 70 recipes from 14th- and 15th-century Catalan and Italian manuscripts, adapted for today's kitchens. Starting with the natural and cultural affinities of Mediterranean Europe, such that a medieval merchant from Italy could be understood in Marseille and Barcelona, it demonstrates the culinary similarities that differentiated this region from northern Europe. This second edition has been extensively revised and enlarged by a third and is lavishly illustrated with images from medieval texts. It includes new sections on the medieval table and table manners, and discusses the significance of the medieval banquet through a selection of menus."--Provided by publisher.
The original Mediterranean cuisine -- The unity of Mediterranean Europe -- The medieval culinary revival -- The hierarchy of food -- The Arab influence -- The scent of spices -- Mediterranean ingredients -- The Mediterranean kitchen -- The Mediterranean table -- Medieval menus and banquets -- Medieval table manners -- Medieval recipe collections -- The recipes : practical considerations -- Recipes -- Sauces -- Meat and poultry -- Fish and seafood -- Vegetables and pulses -- Pies and torte -- Desserts and fritters -- Preserves.
Includes bibliographical references and indexes.
Keywords: Cooking, Mediterranean; Cooking, Medieval; Australian